An introduction to heat pipes modeling, testing, and applications - Peterson, G. P. (John Wiley & Sons New York, 1994)
Your complete resource on heat pipe operation, behavior,performance characteristics, and limitations This book is designed to help students, operations engineers, and mechanical and electrical engineers in the electronic packaging industry grasp the principles of operation for a wide range of heat pipes. Packed with examples and design information, it takes you through the background and historical development of heat pipes,discusses the interfacial phenomena that govern their operational characteristics, and presents the fundamental operating principles and limitations of both heat pipes and thermosyphons. Along with detailed presentations of the governing physicalphenomena involved, this comprehensive guide features extensive coverage of: * The background physics of fluids, their behavior in heat pipes,and associated interfacial phenomena * Heat pipe design methodologies and manufacturing considerations * Applications for cooling both electrical and mechanical systems * The full range of heat pipe classifications, including rotating and revolving, micro, cryogenic, and variable conductance heat pipes, as well as thermal diodes and switches This book provides all the information and guidance you need to increase your understanding of these innovative devices and to begin to apply them to the thermal control of electronic devices and components.
Keywords: Heat pipes